79 Intrathecal outcomes for Palliative patients; York's story. (14th March 2023) - Grewal, Bhajneek; Armstrong, Philippa; Hall, Peter
Abstract : Background: The Chronic Pain Team in York provides externally controlled intrathecal drug delivery systems (ITDD) to palliative patients with intractable pain who are known to the local Palliative Care service. This study reviewed the demographics and outcomes for these patients. Methods: A retrospective case note review was undertaken of all palliative patients who received ITDD between 2013 and 2018. Case notes from York & Scarborough hospitals and hospices were perused to collect data with appropriate permissions. Results: 44 patients underwent ITDD insertion. All had input from the Palliative Care team. The majority of these patients had a malignancy. Local hospices supported 80% of patients post-insertion. Within one week of insertion, pain had completely gone in 16% of patients. In 77%, pain had partially improved. 64% of patients had been suffering with intolerable opiate-related side effects prior to ITDD insertion. Post-insertion, 54% of this group showed a clear improvement in side effects. 73% were affected by complications within 72 hours of insertion, and 60% of patients experienced ongoing complications of some kind. The majority of these were minor complications. In 89% of patients' records, the notes indicated that there was overall benefit in ITDD insertion. 11% of patients lived longer than predicted by Palliative Care. 34% lived as long as predicted, and 55% lived shorter than predicted at the time of ITDD referral. Conclusions: The vast majority of patients and clinicians felt that ITDD insertion was worthwhile, with significant numbers of patients obtaining an improvement in pain. Whilst the complication rate is high, the vast majority of these were minor without patient harm. It is not possible to draw conclusions regarding extension of prognosis in this retrospective study.